ANALISIS PERBANDINGAN PLAT BETON KONVENSIONAL DAN PLAT BETON BONDEK - Prabaswara, Alfian Bagas; Nurdianto, Risnandar (Universitas Perjuangan Tasikmalaya, 2024)
Abstract Floor plates, as an essential element in building structures, play a vital role in supporting structural loads and living (human) loads as well as objects in the room. The purpose of the study is to analyze whether the floor plate structure using bondek products is safe or not in terms of structural strength and identify the amount of cost coMPared to the cost incurred for making floor plates with the bondek method and conventional methods. The structural analysis of the floor plate using the floor plate is to find out whether the floor plate is safe and can be used, which he takes into account referring to PBI-1971 and the Steel Deck Institute, 2011 using SAP2000 and excel. The results of the research that have been carried out have been obtained that conventional and bondek floor plates are both safe to use with the results shown by MUAda>MUPerlu for conventional floor plates and Mru>MUAda for bondek floor plates. The cost incurred shows that it is 29.68% cheaper to make bondek floor plates coMPared to conventional floor plates. Keywords : Plate, Conventional, Bondek, Strength, Cost. Abstrak Plat lantai, sebagai elemen penting dalam struktur bangunan, memainkan peran vital dalam menopang beban struktural dan beban hidup (manusia) serta benda didalam ruangan. Tujuan penelitian untuk menganalisa aman atau tidaknya struktur plat lantai yang menggunakan produk bondek ditinjau dari segi kekuatan struktur dan mengidentifikasi besarnya perbandingan biaya yang dikeluarkan untuk pembuatan plat lantai dengan metode bondek dan metode konvensional. Analisis struktur plat lantai mengacu pada PBI-1971 dan Steel Deck Institute, 2011 menggunakan SAP2000 dan Microsoft excel. Hasil penelitian yang telah dilakukan, diperoleh bahwa plat lantai konvensional dan bondek sama-sama aman digunakan dengan hasil yang ditunjukkan MUAda>MUPerlu untuk plat lantai konvensional dan Mru>MUAda untuk plat lantai bondek. Biaya yang dikeluarkan menunjukkan 29,68% lebih murah pembuatan plat lantai bondek dibandingkan dengan plat lantai konvensional. Kata kunci : Plat, Konvensional, Bondek, Kekuatan, Biaya.